UJI MPN COLIFORM DAN IDENTIFIKASI FUNGI PATOGEN PADA AIR KOLAM RENANG DI KOTA MALANG - Edi Suriaman; Wulandika Putri Apriliasari (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2017)
This study aimed to examine the content of fecal coliform and types of fungi pathogens contained in the water swimming pools in Malang. This study represents a descriptive type of research. The water samples were collected from two swimming pools located around the city of Malang. This study is divided into two: the testing of Coliform bacteria by MPN, and the identification of fungi. Results ofColiformMPN index was compared apply the MPN table. The results of all samples exhibit positive for Coliform, the number of Coliformbacteriacontained in each of the two swimming pools respectively 75 cfu / 100 ml sample, and 43 cfu / 100 ml sample.Based on the identification of the fungus has been conducted, we havedetectedPenicilliumsp., Fusariumsp., Aspergillus sp., Microsporum ferrugineum, and Microsporumaudouinii. The spread of contamination bacterial and fungal pathogens in the water pose a threat to human health.